PKM2 aggregation drives metabolism reprograming during aging process - Bie, Juntao; Li, Ridong; Li, Yutong; Song, Chen; Chen, Zhaoming; Zhang, Tianzhuo; Tang, Zhiheng; Su, Li; Zhu, Liangyi; Wang, Jiaxin; Wan, You; Chen, Jun; et al. (Nature communications, 2024)
While protein aggregation’s association with aging and age-related diseases is well-established, the specific proteins involved and whether dissolving them could alleviate aging remain unclear. Our research addresses this gap by uncovering the role of PKM2 aggregates in aging. We find that PKM2 forms aggregates in senescent cells and organs from aged mice, impairing its enzymatic activity and glycolytic flux, thereby driving cells into senescence. Through a rigorous two-step small molecule library screening, we identify two compounds, K35 and its analog K27, capable of dissolving PKM2 aggregates and alleviating senescence. Further experiments show that treatment with K35 and K27 not only alleviate aging-associated signatures but also extend the lifespan of naturally and prematurely aged mice. These findings provide compelling evidence for the involvement of PKM2 aggregates in inducing cellular senescence and aging phenotypes, and suggest that targeting these aggregates could be a promising strategy for anti-aging drug discovery. PKM2 is involved in the aging process but the mechanism remains elusive. Here, the authors show that PKM2 forms aggregates during aging and identify two small molecules which can dissolve the PKM2 aggregates and delay aging.